Synergistic amelioration of renal oxidative stress, inflammation, and fibrosis by combination of metformin and Clinacanthus nutans leave extracts in a type 2 diabetic rat model - Laorodphun, Pongrapee; Thongyim, Saruda; Suriyaprom, Sureeporn; Maphet, Pornchita; Tragoolpua, Yingmanee; Kaewkod, Thida; Panya, Aussara; Arjinajarn, Phatchawan (Frontiers in Pharmacology, 2025)
BackgroundCombination treatment enhances the therapeutic potential for diabetes, particularly for patients with severe complications. Combining standard therapeutic drugs with alternative bioactive compounds provides a promising option for long-term treatment, given the high safety profile of bioactive substances. Objective in this study, we aimed to evaluate the synergistic effects of metformin and Clinacanthus nutans (Burm. f.) Lindau (CN) on glucose metabolism and renal dysfunction parameters in a type 2 diabetic rat model.MethodsMale Wistar rats were fed a high-fat diet for 4 weeks and then received a low dose of streptozotocin to induce type 2 diabetes. The diabetic rats were randomly divided into four groups: untreated diabetic rats (DM), diabetic rats treated with CN at doses of 100 or 200 mg/kg/day (DM100 or DM200), diabetic rats treated with a combination of CN and metformin (DMCOM), and diabetic rats treated with metformin at 100 mg/kg/day (DMMET). The treatments were administered by gavage for 4 weeks.ResultsCompared to single treatments, DMCOM showed a remarkable effect in reducing several parameters, including serum creatinine and blood urea nitrogen, while enhancing creatinine clearance in diabetic rats. Additionally, DMCOM significantly decreased malondialdehyde levels. Notably, diabetic rats treated with DMCOM exhibited a significant reduction in parameters associated with renal dysfunction, as evidenced by decreased inflammation markers, along with downregulated fibrotic markers.ConclusionOur findings provide a scientific basis for the clinical application of CN and suggest a new strategy for preventing nephrotoxicity and other kidney diseases in diabetic patients.